Yield and Efficiency of Mental Health Screening: A Comparison of Screening Protocols at Intake to Prison - Martin, Michael S; Potter, Beth K; Crocker, Anne G; Wells, George A; Colman, Ian (Université d'Ottawa | University of Ottawa, 2016)
Background The value of screening for mental illness has increasingly been questioned in low prevalence settings due to high false positive rates. However, since false positive rates are related to prevalence, screening may be more effective in higher prevalence settings, including correctional institutions. We compared the yield (i.e. newly detected cases) and efficiency (i.e. false positives) of five screening protocols to detect mental illness in prisons against the use of mental health history taking (the prior approach to detecting mental illness). Methods and Findings We estimated the accuracy of the six approaches to detect an Axis I disorder among a sample of 467 newly admitted male inmates (83.1% participation rate). Mental health history taking identified only 41.0% (95% CI 32.1, 50.6) of all inmates with mental illness. Screening protocols identified between 61.9 and 85.7% of all cases, but referred between 2 and 3 additional individuals who did not have a mental illness for every additional case detected compared to the mental health history taking approach. In low prevalence settings (i.e. 10% or less) the screening protocols would have had between 4.6 and 16.2 false positives per true positive. Conclusions While screening may not be practical in low prevalence settings, it may be beneficial in jails and prisons where the prevalence of mental illness is higher. Further consideration of the context in which screening is being implemented, and of the impacts of policies and clinical practices on the benefits and harms of screening is needed to determine the effectiveness of screening in these settings.
Keywords: screening; mental health; prison; health services